Wildlife Diversity for Ecotourism at Aqua Lestari Forest Park, North Minahasa - Diah , Diah Irawati Dwi Arini; Julianus, Julianus Kinho; Melkianus , Melkianus S Diwi; Margareta , Margareta Christita; Jafred , Jafred E Halawane; Fahmi, Muhammad F Fahmi; Yermias, Yermias Kafiar (Jurnal Wasian, 2018)
The purpose of this study is to know the potential diversity of wild fauna (birds, butterflies, reptils, and mammals) in THAL. Inventory of mammal, reptile, and butterfly using line transect method while birds were observed by Ponctuels d'Abundance Indices method (IPA). The results showed that the potential fauna can be found in THAL as many as 49 species consisting of 36 species of birds, eight species of butterflies, three species of reptiles, and three species of mammals. From 49 fauna species at least nine species were endemic to Sulawesi and 11 species protected by Indonesian law. In the future development of THAL area, it is expected that management will conserve the condition of wildlife habitat in order to stay natural.